Državni zbor po 1. maju - igralec ali zgolj statist na evropskem prizorišču? - Vehar, Primož (Revus (Ljubljana), 2004)
The National Assembly, which according to Slovenian constitutional order provides legislative functions and is the bearer of the legislative branch of power and also the general representative body, will preserve its current functions in the part of transferred competencies to the EU institutions after 1st May 2004, when Slovenia accedes to the EU. It could indirectly participate in the EU legislative process through the government. This is possible not only because of promulgation of constitutional amendments in March last year which supported a new relationship between the Parliament and the Government, but above all because of the Law on Co-operation between the National Assembly and the Government in EU Affairs issuing from constitutional amendments, which is currently in the third reading. Comparative constitutional regulations have shown similar solutions in the Constitutions of Germany, France, Austria, Sweden, Finland and Hungary, which are also solving the Parliament -Government relationship on the same constitutional level, regarding EU affairs. The procedure of amending the Slovene Constitution was held parallel with the EU reform process, whose key task has been the delivery of a greater role to National Parliament in the decision making process. The role of the National Assembly after 1st May will depend mostly on the National Assembly itself, as well as on the manner and quality of the co-operation with the Government in the formation of common Slovene viewpoints in the EU legislative process.
Keywords: državni zbor; Evropska unija; parlamenti; Slovenija; zakonodaja